2004
DOI: 10.1002/cbf.1109
|View full text |Cite
|
Sign up to set email alerts
|

Glucose and glutamine utilization by rat lymphocytes, monocytes and neutrophils in culture: a comparative study

Abstract: Glucose and glutamine utilization and production of glutamate and lactate were determined for up to 48 h in lymphocytes, monocytes and neutrophils cultured in medium rich in metabolites and vitamins. Glucose was utilized by the three cell types in culture in the following order: neutrophils > monocytes > lymphocytes, whereas lactate was produced in the order: monocytes > neutrophils > lymphocytes. The consumption of glucose followed the activity of glucose-6-phosphate dehydrogenase but it was not related to he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1
8

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 30 publications
2
50
1
8
Order By: Relevance
“…The underlying thesis is, that in anabolic situations not only a raised pyruvate uptake, but also a substantial amount of de novo intracellular pyruvate as well as pyruvate-dependent metabolite synthesis occurs [37]- [39]. And indeed, our results seem to confirm this hypothesis, because following pyruvate incubation increased glutamate, glutamine, aspartate (asparagine), alanine, α-ketotglutarate but also to serine and glycine concentrations have intracellularly been found (i.e.…”
Section: Pyruvate Induced Effects: Is There An Impact By Adding a Glusupporting
confidence: 75%
“…The underlying thesis is, that in anabolic situations not only a raised pyruvate uptake, but also a substantial amount of de novo intracellular pyruvate as well as pyruvate-dependent metabolite synthesis occurs [37]- [39]. And indeed, our results seem to confirm this hypothesis, because following pyruvate incubation increased glutamate, glutamine, aspartate (asparagine), alanine, α-ketotglutarate but also to serine and glycine concentrations have intracellularly been found (i.e.…”
Section: Pyruvate Induced Effects: Is There An Impact By Adding a Glusupporting
confidence: 75%
“…Gln is characterized as a functional amino acid because it serves as a precursor for (1) purine and pyrimidine synthesis leading to DNA and RNA synthesis; (2) the production of NADPH for superoxide production in phagocytes; (3) oxidation for energy; and (4) nitric oxide production by macrophages (Newsholme et al, 1999;Furukawa et al, 2000;Pithon-Curi et al, 2004). To our knowledge, the fate of utilized Gln in bovine leukocytes has not been metabolically characterized.…”
Section: Glnmentioning
confidence: 99%
“…Studies have shown that Gln is generally used by lymphocytes at high rates, well above requirements (i.e. .100-fold) for other metabolic processes, because of rapid cell division that is not observed in terminally differentiated cells such as PMN and macrophages (Newsholme et al, 1999;Pithon-Curi et al, 2004).…”
Section: Glnmentioning
confidence: 99%
“…For proper demonstration of the beneficial effects associated with the improved oxygen carrying capacity in GV-supplemented medium, it was important that cell growth was not limited by any factor other than the availability of oxygen to the (2) accumulation of inhibitory metabolites such as lactate (Nahapetian et al 1986;Pithon-Curi et al 2004) and ammonia (Imamura et al 1982;Thilly et al 1982;Wong et al 2004). These were carefully eliminated in the perfusion culture study, as described in the following: The circulating medium was changed every 2 days.…”
Section: Perfusion Culture Studiesmentioning
confidence: 99%